2020
DOI: 10.1371/journal.pone.0243834
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines safety and maternal knowledge for enhanced maternal immunization acceptability in rural Uganda: A qualitative study approach

Abstract: Background Maternal immunization is a successful and cost-effective public health strategy. It protects pregnant women and their infants from vaccine-preventable diseases. Uganda is exploring new vaccines for pregnant women like replacing Tetanus Toxoid (TT) with Tetanus-Diphtheria (Td). Research on knowledge, attitudes, beliefs, and willingness among pregnant women is needed before the introduction of vaccines for pregnant women. This study was aimed at exploring maternal knowledge, attitudes, willingness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…As much as the healthcare workers would like to maintain a high vaccine coverage, issues such as delays in vaccine delivery to the health facilities meant that even when mothers showed up and demanded to be vaccinated the vaccines were out of stock, causing a missed opportunity. Similar to what has been found in Ethiopia (Gebremichael et al 2018), Tanzania (Maluka et al 2020) and Uganda (Kajungu et al 2020), we observed that if a health care worker was harsh, abusive or rude, it could discourage women from attending ANC clinics, which has a ripple effect on uptake of vaccines by the mothers.…”
Section: Discussionsupporting
confidence: 85%
“…As much as the healthcare workers would like to maintain a high vaccine coverage, issues such as delays in vaccine delivery to the health facilities meant that even when mothers showed up and demanded to be vaccinated the vaccines were out of stock, causing a missed opportunity. Similar to what has been found in Ethiopia (Gebremichael et al 2018), Tanzania (Maluka et al 2020) and Uganda (Kajungu et al 2020), we observed that if a health care worker was harsh, abusive or rude, it could discourage women from attending ANC clinics, which has a ripple effect on uptake of vaccines by the mothers.…”
Section: Discussionsupporting
confidence: 85%
“…This could be due to the fact that tetanus toxoid vaccination during pregnancy is integrated into antenatal care [10], leading to participants' confusion and difficulty in differentiating between interventions or, as we found, due to the perception that all medication that protects against infection is a "vaccination". A study in Eastern Uganda also identified issues with women describing antimalarial medication as a vaccine, which highlights the need for future public information campaigns to focus on the meaning of vaccination [11].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is limited evidence on factors that may influence pregnant women's acceptance and refusal of maternal vaccination in Uganda that could be used to inform public health programmes [11]. However, studies in other countries report various factors that affect vaccination uptake; for example, in Somalia, concerns about vaccine safety and limited knowledge were mentioned to have affected vaccine uptake among the women [12].…”
Section: Introductionmentioning
confidence: 99%
“…A study in the western part of Uganda showed that the involvement of mothers enhances adhering to prompt vaccination of their children (Vonasek et al, 2016 ). Pregnant women who have experienced maternal vaccination are willing to receive new vaccines If they are sensitised about new vaccines (Kajungu et al, 2020 ). The participant willingness to take part in a vaccine trial targeting schistosomiasis has also been noted in several fishing communities in Uganda (Sanya et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%